Pengaruh Curah Hujan pada Kegagalan Tegangan Impuls IsolatorTegangan Tinggi. - Perpustakaan UGM, i-lib ([Yogyakarta] : Center For Food and Nutritions Studies Gadjah Mada University, 1999)
ABSTRAK The design of transmission and distribution lines suspension insulators is so that flashover may not occur in all condition, Fo this reason, enviromental condition : temperature, pressure, humidity and rain should be taken into account. In this research, rain was the main parameter investigated due to its conductive characteristic because, in fact, ou water of which containing dust material, that may be conductive, coming out as wast material from industries. An artificial rain equipment has been made enables to produce rain with different level of heaviness by controlling its electrical water pumping motor. Futher, simulating the angle of real rain fall can be done by mechanically moving of water spraying equipment. Four supension insulators of two different types were investigated. The results showed that the heavier the rainfall the less voltage breakdown of insulators produced. Moreover, vertically rainfall correlates to the less voltage breakdown